Functional-guided radiotherapy using knowledge-based planning. Issue 3 (December 2018) - Faught, Austin M.; Olsen, Lindsey; Schubert, Leah; Rusthoven, Chad; Castillo, Edward; Castillo, Richard; Zhang, Jingjing; Guerrero, Thomas; Miften, Moyed; Vinogradskiy, Yevgeniy
Abstract: Background and purpose: There are two significant challenges when implementing functional-guided radiotherapy using 4DCT-ventilation imaging: (1) lack of knowledge of realistic patient specific dosimetric goals for functional lung and (2) ensuring consistent plan quality across multiple planners. Knowledge-based planning (KBP) is positioned to address both concerns. Material and methods: A KBP model was created from 30 previously planned functional-guided lung patients. Standard organs at risk (OAR) in lung radiotherapy and a ventilation contour delineating areas of high ventilation were included. Model validation compared dose-metrics to standard OARs and functional dose-metrics from 20 independent cases that were planned with and without KBP. Results: A significant improvement was observed for KBP optimized plans in V20Gy and mean dose to functional lung ( p  = 0.005 and 0.001, respectively), V20Gy and mean dose to total lung minus GTV ( p  = 0.002 and 0.01, respectively), and mean doses to esophagus ( p  = 0.005). Conclusion: The current work developed a KBP model for functional-guided radiotherapy. Modest, but statistically significant, improvements were observed in functional lung and total lung doses.